PEMBUATAN DAN PENENTUAN SPESIFIKASI SENSOR GAYA BERAT BERBASIS PEGAS DAN LDR - Muhammad Fuad (PILLAR OF PHYSICS, 2013)
Objective of this reseach are to investigate the performance spesification and the design spesification of gravity force sensor base on spring and LDR. Data is collected by direct measurement and indirect measurement. Direct measurement is done to measure mass of object and output voltage of sensor. Indirect measurement is done to determine the accuracy and the precision of gravity force sensor. Data is analized by error theory and graph method. There are two mains result of this record. First, performance spesification consist of drawing-spring, LDR, signal conditioning circuit that convert weight of object into resistance and then into output voltage. Second, transfer function sensitivity of gravity force sensor is directly proportional with initial voltage is 1,516 Volt and sensitivity is 6,013 Volt/Newton. Accuracy and presicion of gravity force sensor are high, respectly 98,59 % and 0,999 Keyword: Gravity Sensor, LDR, Spring, Spesification Performance, Spesification Design